Checklisten in der Hausarztpraxis – eine Entwicklungsstudie mit Vorher/Nachher-Vergleich - Saggau, Korbinian; Höfle, Anina; Schedlbauer, Angela; Hueber, Susann; Roos, Marco; Kühlein, Thomas; Heinmüller, Stefan (Zeitschrift für Allgemeinmedizin, 2021)
Background Quality assurance in Germany focuses on support processes (requirements of hygiene etc.) rather than on quality of care (QOC). Systems that do focus on QOC are referred to as “clinical governance” (CG). We understand CG as a process of professional self-reflection and management. An electronic checklist (eCL) for Chronic Obstructive Lung Disease (COPD) was developed reminding doctors of important aspects of care, assuring adequate documentation, and generating data at the same time. We describe the development of the eCL and a before/ after analysis of process-QOC for COPD-patients in a single group family practice. Methods Developmental study with a before/after-analysis. To capture QOC at baseline (t0) electronic health records (EHR) of COPDpatients were surveyed using a guideline-based questionnaire. Our intervention was an eCL, which can be used within the EHR. Doctors and practice assistants were trained in the application of the eCL, its use remained optional. One year (t1) and four years (t2) after implementation QOC was reanalysed. Results At t0 103 COPD patients were identified. For 58% a spirometry was documented. Smoking status was recorded in 56% and 34% were vaccinated against influenza. After introduction of the eCL due to some changes in the practice 80 patients at t1 and 49 patients at t2 were identified. For 71% (t1) and 63% (t2) a spirometry was documented. Smoking status was documented in 75% (t1) and 90% (t2). Influenza vaccination was documented in 33% (t1) and 55% (t2) of patients. Conclusions Development and implementation of an eCL in the setting of our office within the EHR was possible. Our results indicate that the provision of an eCL together with a short introduction can help improve QOC. The eCL allows doctors to perform CG autonomously.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Checklist; Chronic disease; Evidence-based medicine; Family medicine; General practice

Laying the foundation for an ICF core set for community dwelling older adults in primary care: an expert survey Entwicklung eines ICF-Core-Sets für ältere Patienten in der Hausarztpraxis: eine Expertenumfrage - Gotthardt, Susann; Tomandl, Johanna; Höfle, Anina; Kühlein, Thomas; Book, Stephanie; Graessel, Elmar; Talaska, Michael; Sieber, Cornel; Freiberger, Ellen (Zeitschrift für Gerontologie und Geriatrie, 2021)
Background: A holistic biopsychosocial model focused on functioning in individual contexts (environment, task) is better suited to meet the needs of older patients than disease only based models. The International Classification of Functioning, Disability and Health (ICF) is the official standard for describing functional health. As the ICF is too detailed to be used in practice, brief core sets have been developed. Objective: This study aimed to identify relevant aspects of functioning for older primary care patients from the perspective of healthcare professionals in Germany. Material and methods: An internet-based cross-sectional expert survey was conducted in preparation for the development of an ICF core set for community-dwelling patients aged 75 years and older. Open-ended questions to identify the most important aspects of functioning and disability in old age were used. Responses were analyzed based on a content analysis approach to identify relevant concepts in the care of the target population. These concepts were then linked to ICF categories according to established linking rules. Results: A total of 63 experts participated in this survey. Across all responses, 2240 meaningful concepts were identified. A total of 75 ICF categories (4 first level categories, 67 second level categories, 4 code combinations) were identified by at least 5% of respondents and will thus be considered as candidate categories for the final ICF core set. Most of concepts were associated with the environmental factors component. The most frequently identified categories were immediate family and family relationships. Conclusion: This survey provides a list of relevant ICF categories from the experts’ perspective and together with other preparatory studies will be used for developing an ICF core set for community-dwelling older adults in primary care.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Community-dwelling older patients; Expert survey; Functioning; ICF core set; Primary care

Laying the foundation for a primary care core set of the international classification of functioning, disability and health (icf) for community-dwelling older adults: A qualitative study - Tomandl, Johanna; Book, Stephanie; Höfle, Anina; Grässel, Elmar; Sieber, Cornel; Freiberger, Ellen; Kühlein, Thomas; Hueber, Susann; Gotthardt, Susann (Journal of Rehabilitation Medicine, 2021)
Objective: To explore relevant areas of functioning from the perspective of community-dwelling adults aged 75 years and over, in order to develop a Core Set of the International Classification of Functioning, Disability and Health (ICF) for community-dwelling older adults for use in primary care. Design: Qualitative study using semi-structured interviews and focus groups. Participants: A total of 27 community-dwelling older adults participated in the interviews and 24 of them in the focus groups. Methods: Following the proposed methodology of the ICF Research Branch, this is 1 of 4 preparatory studies in the Core Set development process. Within the transcripts, concepts of functioning were identified, based on Mayring s qualitative content analysis using deductive category assignment with the ICF being the category system. Results: Overall 6,667 concepts were identified. Most were linked to the Activities and Participation component. The most frequently identified categories were "recreation and leisure" and "family relationships". Conclusion: Categories from all ICF chapters were identified, demonstrating the complexity and multidimensionality of the ageing process, with a special emphasis on the component Activities and Participation. This qualitative study provides a list of relevant categories from the perspective of community-dwelling elderly people, which will be used to develop a Core Set for older primary care patients.
CRIS-Team Scopus Importer:2021-03-26
Keywords: aged; cross-sectional study; Disability and Health; focus group; general practice/methods.; geriatric assessment/ methods; independent living; International Classification of Functioning; interviews as topic

The quality of COPD care in German general practice—A cross-sectional study - Heinmüller, Stefan; Schaubroeck, Emmily; Frank, Luca; Höfle, Anina; Höfle, Anina; Langer, Michael; Saggau, Korbinian; Schedlbauer, Angela; Kühlein, Thomas (Chronic Respiratory Disease, 2020)
Objectives: Chronic Obstructive Pulmonary Disease (COPD) is a common health problem to be dealt with in primary care. Little is known about the quality of care provided for patients with COPD in Germany. Therefore, we wanted to assess the current quality of care delivered by a primary care network (PCN) for patients with COPD. Methods: A cross-sectional study was conducted in collaboration with a primary care network (PCN). All patients of the PCN aged 40 years and older with a diagnosis of COPD were identified through electronic health records (EHR). A set of quality indicators (QIs) developed in accordance with current COPD-guidelines were appraised through numerical data retrieved from the EHR. Results: In total, 2,568 patients with COPD were identified. Their mean age was 67 (SD±12) years, 49% were male. Thirty-five percent had a parallel diagnosis of asthma. There was no documentation of any spirometry for 54% of patients; 29% had a spirometry within the previous year. An influenza vaccination was documented for 37% within the preceding 12 months; 12% received a pneumococcal vaccination in the last 6 years. Smoking status was documented for 44% within the last year. Conclusion: The quality of care for patients with COPD in the PCN seemed suboptimal, despite the presence of a Disease Management Program (DMP). This finding is likely to apply widely to German general practice. Quality assessment through currently available EHR data was challenging due to non-standardized and insufficient documentation.
CRIS-Team Scopus Importer:2020-12-11
Keywords: chronic obstructive; documentation; general practice; practice guideline; Pulmonary disease; quality of health care